Uji Antioksidan Ekstrak Etanol Bunga Telang (Clitoria ternatea L.) dan Formulasi Salep pada Penyembuhan Luka Sayat Punggung Kelinci Putih New Zealand - Khusnul Hotimah; Iswandi Iswandi; Jena Hayu Widyasti (Politeknik Kaltara, 2023)
Telang flower (Clitoria ternatea L.) has antioxidant effects because it contains compounds such as phenols, anthocyanins, flavonol glycosides, kaempferol glycosides, terpenoids, steroids, flavonoids, and tannins. This study aims to determine whether telang flower ethanol extract has antioxidant activity, whether telang flower ethanol extract ointment can heal cuts in rabbits and determine the effective concentration of telang flower ethanol extract ointment for healing cuts in rabbits. This study used telang flower extract macerated with 70% ethanol. The concentration of the extract was made as much as 3, namely 0.1%, 0.2%, 0.4%. The extract was tested for antioxidant activity using the DPPH method. The tested extract was then made into an ointment and applied to the rabbit's back, and wound healing was observed. Based on the results of statistical tests using SPSS®, variations in the concentration of the ethanol extract of the butterfly pea flower affected the antioxidant activity. The 0.2% concentration gave a significant difference compared to the 0.1% and 0.4% concentrations. Telang flower ethanol extract ointment can heal the incision wound on the rabbit's back. Based on the results of statistical tests using SPSS® on the healing of cuts in rabbits showed a significant difference. The 0.2% concentration differed significantly from the 0.4% concentration, where the time required for the 0.2% concentration was faster than the 0.4% concentration.